Pendokumentasian Aplikasi Ragam Hias Budaya Bali, Sebagai Upaya Konservasi Budaya Bangsa Khususnya pada Perancangan Interior - Hartanti, Grace; Nediari, Amarena (Humaniora, 2014)
Various ornament of Indonesian people comes from the ethnic groups from all over the archipelago. As a tangible cultural ornament has a specific purpose and it does not change throughout the ages. Bali is one of the ethnic group in archipelago that has beautiful decorative art and one of the most popular tourism destination in Indonesia. Bali?s ornament generally seen as decorative carving on the column, window or even in door. The beauty of Bali is not only as an inspiration for their colors and sculpture but also the variety of forms that have been simplified in the ornament. Moreover, floral & fauna forms are easy to apply as an interior element in modern buildings. Generally the value of these ornament has a specific purpose related to the cultural and social custom in Bali people. So that the application need to consider more about the purpose of the symbol of the ornament.